1997
DOI: 10.1111/j.1559-1816.1997.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending Models of Prosocial Behavior to Explain University Alumni Contributions1

Abstract: Survey data merged with contribution records from a development office database provided a basis for understanding alumni support for a university. The survey randomly sampled alumni of a state university school of management who had graduated between 1980 and 1988. Subjects filled out mail questionnaires measuring social psychological constructs from the literature on prosocial behavior. The determinants of obligation to donate included perceived efficacy, perceived need, reciprocity, and individual attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 23 publications
2
53
0
2
Order By: Relevance
“…In turn, responsibility feelings increase feelings of moral obligation to act prosocially, and these feelings of obligation induce prosocial behavioral intentions. These results are in line with studies that have proposed that awareness of consequences affect ascription of responsibility and that responsibility indirectly affects intentions and behavior via PN (Black et al, 1985;De Ruyer & Wetzels, 2000;Diamond & Kashyap, 1997;Steg et al, 2005;Stern, 2000). A mediator model also seems theoretically plausible because it is difficult to feel responsible for acting prosocially or to think about the effectiveness of possible actions without knowing whether not acting prosocially is a problem.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In turn, responsibility feelings increase feelings of moral obligation to act prosocially, and these feelings of obligation induce prosocial behavioral intentions. These results are in line with studies that have proposed that awareness of consequences affect ascription of responsibility and that responsibility indirectly affects intentions and behavior via PN (Black et al, 1985;De Ruyer & Wetzels, 2000;Diamond & Kashyap, 1997;Steg et al, 2005;Stern, 2000). A mediator model also seems theoretically plausible because it is difficult to feel responsible for acting prosocially or to think about the effectiveness of possible actions without knowing whether not acting prosocially is a problem.…”
Section: Discussionsupporting
confidence: 74%
“…A large amount of studies show, however, that intentions are closely linked to behavior (see Armitage & Conner, 2001). Subsequently, most studies that tested the NAM included only self-reported behavior (e.g., De Ruyter & Wetzels, 2000;Diamond & Kashyap, 1997;Guagnano, 2001;Nordlund & Garvill, 2002Steg et al, 2005;Stern, 2000;Tyler et al, 1982;Van Liere & Dunlap, 1978). Choosing similar dependent measures as these studies makes comparing results easier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the variable, " perceived need for fi nancial support " has been shown in many studies to be an important predictor of alumni giving ( Miracle, 1977 ;House, 1987 ;Taylor and Martin, 1995 ;Diamond and Kashyap, 1997 ). Similarly, Pearson's (1999) research found that a signifi cant deterrent to giving is a feeling among alumni that the university does not need their gifts as much as other nonprofi t organizations.…”
Section: Expectancy Theorymentioning
confidence: 99%
“…With the increasing competitiveness in the market, combined with rising educational costs and reductions in student fi nancial aid, college and university alumni are ever more essential in providing fi nancial support to their institutions ( Briechle, 2003 ;Liu, 2006 ;Weerts and Ronca, 2007 ). Research on giving to higher education generally has focused on predicting the factors and characteristics of alumni who give (e.g., Taylor and Martin, 1995 ;Baade and Sundberg, 1996 ;Okunade and Berl, 1997 ;Belfi eld and Beney, 2000 ;Clotfelter, 2003 ;Weerts and Ronca, 2007 ), the institutional and macroeconomic factors in explaining variations in giving (e.g., Briechle, 2003 ;Gunsalus, 2004 ;Liu, 2006 ), alumni motivation for giving (e.g., Diamond and Kashyap, 1997 ;Weerts and Ronca, 2007 ), fundraising practices in higher education (e.g., Harrison, 1995 ;Harrison et al , 1995 ), and the determinants of donor revenue (e.g., Cunningham and Cochi-Ficano, 2001 ; see review of literature in Liu, 2006 ).…”
Section: Purpose Of the Studymentioning
confidence: 99%